The Effect of Compensation and Career Development on Employee Performance with Work Discipline as a Moderation Variable (Case Study at PT Kencar Sukses Investama) - Insanosa Fauzan Ramadhan; Bustanul Arifin Noer (International Journal of Business and Management Technology in Society, 2024)
Purpose – This research aims to investigate the effect of compensation and career development on employee performance, with work discipline as a moderating variable. This research aims to understand the extent to which compensation and career development influence employee performance, as well as whether work discipline plays a role as a moderating factor in the relationship between compensation and career development and employee performance at PT. Kencar Sukses Investama. Methodology – A quantitative approach with a purposive sampling technique is used in this research methodology. The research sample comprised of 151 PT. Kencar Sukses Investama workers. The data was gathered using the Partial Least Squares (PLS) Structural Equation Modeling (SEM) analytical tool. Compensation, career advancement, work discipline, and employee performance are also factors in this study. Findings – The findings of this research are that career development has a significant influence on work discipline and employee performance, while compensation does not have a significant influence on work discipline and employee performance. Practical implications – The practical implication of this research is the need to pay attention to fair compensation and employee career development as important factors in improving work discipline and employee performance at PT. Kencar Sukses Investama. Social implications – This research can have social implications related to improving employee welfare and organizational efficiency through fair compensation, good career development, and high work discipline.